T-labs and climate change narratives: Co-researcher qualities in transgressive action–research. Issue 1 (March 2019) - Macintyre, Thomas; Monroy, Tatiana; Coral, David; Zethelius, Margarita; Tassone, Valentina; Wals, Arjen EJ
This paper addresses the call for more action-based narratives of grassroot resistance to runaway climate change. At a time when deep changes in society are needed in order to respond to climate change and related sustainability issues, there are calls for greater connectivity between science and society, and for more inclusive and disruptive forms of knowledge creation and engagement. The contention of this paper is that the forces and structures that create a disconnect between science and society must be 'transgressed'. This paper introduces a concept of Transgressive Action Research as a methodological innovation that enables the co-creation of counter hegemonic pathways towards sustainability. Through the method of the Living Spiral Framework, fieldwork reflexions from the Colombian case study of the international T-Learning project were elicited, uncovering and explicating the transgressive learning qualities needed to respond to climate change. As part of a larger action–research project, this paper combines the arts with the social sciences, demonstrating how the concept of 'Transgressive Action Research' can enable co-researchers to engage in disruptive and transformative processes, meeting the need for more radical approaches to addressing the urgent challenges of climate change.